Training related ENT morbidity: a study amongst cadets of a military training institute - Raj, Poonam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Military training involves a harsh and rigorous regimen leading to inadvertent injury and bodily dysfunction. The ear, nose and throat are vulnerable given the nature of the training, which invariably involves combative sports and organized firing practice, which may lead to increased morbidity. This article is based on a population study of training related ENT morbidity amongst cadets undergoing training at a military institute. Methods: The study was carried out in three parts including determinations of morbidity statistics due to ENT illnesses amongst cadets during training, awareness levels and attitudes of cadets towards common ENT ailments and effect of military training on the audiometric parameters. Results: Daily cadet sick report was 250 – 270 a month with 21% being respiratory/ENT in nature. Of these 33% were nasal trauma, 18% ear ache with uri, 12% hearing loss/tinnitus, 25% throat symptoms and 12% with allergic symptoms. Overall incidence of hearing loss during the study period was 60.1 per thousand per year, which was mostly transitory. Conclusions: Injuries caused due to training lead to loss of motivation and reduction in combat efficacy as a result of decreased training time. Increasing awareness and better planned training schedules are the need of the hour.